Meningkatkan Daya Saing Produk Melalui Inovasi Label dan Kemasan Pada UMKM di Desa Ngampungan, Kecamatan Bareng, Kabupaten Jombang - Amilia Eka Putri; Dona Wahyuning Laily; Mu’tasim Billah (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
The MSME sector plays a large and important role in the development of the national economy and the regional economy. For the regional economy, MSMEs can increase income, reduce unemployment in villages and can increase their entrepreneurial experience.  Ngampungan Village has a variety of MSMEs that have the potential to improve people's welfare.  However, the problem faced by UMKM in Ngampungan Village is the lack of knowledge about product branding.  Not a few MSME products from Ngampungan Village still don't have labels and use packaging that seems old-fashioned and less attractive.  The purpose of this service is to provide assistance in the manufacture and renewal of labels and packaging to make them more attractive and competitive with competitors.  The methods used in this service are surveys, interviews and discussions, as well as implementation.  The results obtained in this service are the creation of new labels and packaging, as well as increased knowledge of MSME partners in Ngampungan Village regarding packaging and labels that comply with terms and conditions.